Production sector of ornamental rocks: a systematic literature review (Research, Society and Development, 2022)
Understanding the historical point of view about the extraction of ornamental rocks attests to the economic and cultural significance of these materials throughout the development of the most distinct civilizations. However, the mining of ornamental rocks has very specific individualities compared to other extractive industries. Therefore, it is intended through a systematic review of the literature, to recognize through national and international publications, experiences of extraction of ornamental rocks that have been carried out on actions of the feasibility of exploitation, mineral economy, and public policies that can promote the advancement of the extractive sector and the regional development of the state of Goiás.